2020
DOI: 10.1177/2325967120951554
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Distal Femoral Osteotomy Survivorship: Data From the California Office of Statewide Health Planning and Development (OSHPD) Registry

Abstract: Background: Malalignment of the lower extremity can lead to early functional impairment and degenerative changes. Distal femoral osteotomy (DFO) can be performed with arthroscopic surgery to correct lower extremity malalignment while addressing intra-articular abnormalities or to help patients with knee osteoarthritis (OA) changes due to alignment deformities. Purpose: To examine survivorship after DFO and identify the predictors for failure. Study Design: Case series; Level of evidence, 4. Methods: Data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…For each increase in year, the risk of TKA increased 7% in the DFO cohort, while in the HTO cohort, age greater than 40 conferred a 5.0 times higher risk of TKA (95% CI [2.59, 10.9]]). These findings are supported by prior survival analyses, in which older age was associated with higher conversion to TKA in both HTO and DFO [22, 31], and support older age as a relative contraindication to these osteotomies. In the both HTO and DFO cohorts, younger age was associated with increased risk of subsequent arthroscopy, both with and without cartilage procedures.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…For each increase in year, the risk of TKA increased 7% in the DFO cohort, while in the HTO cohort, age greater than 40 conferred a 5.0 times higher risk of TKA (95% CI [2.59, 10.9]]). These findings are supported by prior survival analyses, in which older age was associated with higher conversion to TKA in both HTO and DFO [22, 31], and support older age as a relative contraindication to these osteotomies. In the both HTO and DFO cohorts, younger age was associated with increased risk of subsequent arthroscopy, both with and without cartilage procedures.…”
Section: Discussionsupporting
confidence: 79%
“…When considering survival free of any reoperation, a large study of UKAs and TKAs found a 93% and 96% survival free of reoperation, respectively [20], suggesting that arthroplasties carry a lower risk of reoperation than joint-sparing procedures. Several survival analyses of HTO and DFO have been published in the literature, with recent studies inding an 80% 5-year survival rate for HTO and a 90.2% 5-year survival rate for DFO [22,31]. The present study provides an earlier time point and demonstrates that in the short term, HTO and DFO rarely require revision to arthroplasty.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In particular, predictors associated with the failure of this technique are advanced age, hypertension, asthma, a diagnosis of osteoarthrosis, or traumatic arthropathy at the time of surgery. 27 Furthermore, the medium-term results of TKA after KO are comparable to arthroplasty performed as a primary procedure. Still, crucial aspects of achieving satisfactory results are proper soft tissue balance and correct mechanical axis.…”
Section: Discussionmentioning
confidence: 94%
“… 6 Risks for complications or lower survivorship in the literature include smoking, concomitant cartilage or ligament procedures, surgical indication for arthritis, and other medical conditions. 6 , 7 One of the most common complications of a distal femoral osteotomy is symptomatic hardware. 5 , 8 , 9 The authors aim to limit this complication by their plate-positioning tips.…”
Section: Discussionmentioning
confidence: 99%